2021
DOI: 10.21203/rs.3.rs-378991/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-1β and IL-1ra are key regulators of the inflammatory response to RNA vaccines

Abstract: Excessive systemic inflammation is characteristic to various acute conditions including sepsis, viral infections and immunotherapy-induced adverse events such as cytokine release syndrome (CRS). Recently, several clinical trials evaluating variants of lipid-formulated RNA vaccines for either cancer or COVID-19 have reported systemic inflammatory responses that limit vaccine dosing in humans. Preclinical studies in inbred laboratory mice failed to predict these adverse events, suggesting the existence of underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recently, limitations have been found when predicting clinical outcome based on data generated in murine models regarding downstream effects of systemic inflammation induced by stimulation of toll-like receptor (TLR) 7/8 by mRNA lipoplexes. 45 It has been reported that humans secrete pro-inflammatory interleukin (IL)-1b, whereas mice upregulate the induction of the IL-1 receptor antagonist to control inflammation. Another challenge in this area is the fact that the lipid components themselves may activate immune responses that may differ depending on the type of component and formulation.…”
Section: These Authors Contributed Equallymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, limitations have been found when predicting clinical outcome based on data generated in murine models regarding downstream effects of systemic inflammation induced by stimulation of toll-like receptor (TLR) 7/8 by mRNA lipoplexes. 45 It has been reported that humans secrete pro-inflammatory interleukin (IL)-1b, whereas mice upregulate the induction of the IL-1 receptor antagonist to control inflammation. Another challenge in this area is the fact that the lipid components themselves may activate immune responses that may differ depending on the type of component and formulation.…”
Section: These Authors Contributed Equallymentioning
confidence: 99%
“…In an elegant study comparing LNPs and lipoplexes, differences were found in cytokine induction, which indicate that the ionizable lipid of the LNP formulation is likely responsible. 45 With this in mind, future research on mRNA immunological downstream effects after application, which could affect the safety profile of the mRNA, needs to be cautiously investigated, and the type as well as the composition of an mRNA formulation needs to be selected carefully depending on the disease.…”
Section: These Authors Contributed Equallymentioning
confidence: 99%
“…68 However, it should be noted that some animal studies show no significant difference in protein production between unmodified and modified mRNA, as well as between HPLC-purified and silica-purified mRNA, indicating that these effects are likely to be dependent on the delivery platform, specific mRNA sequence, and animal species. [69][70][71] Finally, circular RNA constructs have been developed as potent expression vehicles 72 and confer nuclease resistance by removing end motifs that may also be important for detection by PRRs. Studies have shown that the use of circular mRNAs can result in significantly decreased activation of innate immunity and improved protein production relative to their unmodified linear counterparts 72,73 As with free siRNA and mRNA in serum, unencapsulated RNA is susceptible to degradation within various compartments of transfected cells.…”
Section: Reviewmentioning
confidence: 99%